Gestión operativa y sus efectos en el crecimiento económico de la Compañía representaciones Alexandpris S.A. Ciudad de Santo Domingo, Período 2014, Reingeniería de procesos operativos. - Terán Silva, Jakson Stalyn (2016)
This research was conducted in Representations Alexandpris SA Company dedicated to the service of logistics in the province of Santo Domingo de los Tsáchilas, offering innovative services, since 1994.The main objectives are to investigate the operational management and its relationship with economic growth, since in Ecuador have increased government policies such as the National Development Plan, which contribute to improving public organization, the welfare of society and families. The analysis of the operational management in Alexandpris SA it exposes the weaknesses and simultaneously transform these into strengths so the proposal is subject to the specific needs of the company is designed to correct operational failures allowing implementing strategies to ensure increased sales and positioning the company the market. The purpose of this research is to increase the number of customers from this work because it will be that the expected outcome of the directors of the company in order to cover the installed capacity of the company and thus increase profits the same. The change in operating structure creates better procedures and improving workers' skills in working times, reducing complaints and improving the work environment. Service quality generates better user feedback to suppliers generating better corporate image, this benefits the company because it is easier to offer the service to manufacturers of different products in Ecuador.